Integration and underdevelopment in the Commonwealth Caribbean - Ramesh Ramsaran (Intereconomics, 1977)
While the integration process in the Caribbean Community and Common Market (Caricom) has only been in force for a few years, it is, in the author's view, clear that the narrow free trade approach used so far will not be able to deal with the widening gap between the better-off and the less well-off member states or to provide a solution to fundamental problems facing the region as a whole.
Keywords: 330; Integration